Rare occurrence of triple primary malignant tumors: Dermatofibrosarcoma protuberans, lung adenocarcinoma and papillary thyroid carcinoma in a patient with genetic evaluation - Luan Minh Bao Tran; Minh Duc Do; Truong Hung Nguyen; Ngoc-Minh Vuong (Radiology Case Reports)
Triple primary malignancies are rare, involving the occurrence of three distinct, unrelated cancers in a single patient, requiring a personalized, multidisciplinary treatment approach. A 69-year-old male was diagnosed with dermatofibrosarcoma protuberans (DFSP), lung adenocarcinoma, and papillary thyroid carcinoma. After amputation for DFSP, following staging and genetic evaluation, a multidisciplinary tumor board designed a tailored treatment plan, adjuvant chemotherapy for lung adenocarcinoma while monitor regularly the thyroid carcinoma via ultrasound. This case highlights the extreme rarity of this triple primary cancers combination and emphasizes the need for individualized treatment planning. Each cancer's unique characteristics, prognosis, and potential interactions must be considered, alongside the patient's overall health and treatment tolerability, to optimize outcomes in such complex cases.